IQGAP1 is overexpressed in hepatocellular carcinoma and promotes cell proliferation by Akt activation - Chen, Feng (Korean Society for Biochemistry and Molecular Biology, 2010)
The scaffold protein IQGAP1 shows elevated levels in several cancer types, but its expression in hepatocellular carcinoma is unknown. We found that 58% of human hepatocellular carcinoma tissue samples had increased IQGAP1 expression compared to adjacent normal tissue. Overexpressing IQGAP1 raised the in vivo tumorigenicity of hepatocellular carcinoma cells, and forced overexpression of IQGAP1 in vitro stimulated cell proliferation. Cell growth was reduced by knockdown or mutation of IQGAP1, or by treatment of cells with a phosphotidylinositol 3-kinase inhibitor. To determine the mechanism by which IQGAP1 overexpression affected hepatocellular carcinoma cells, we confirmed its interaction in these cells with mammalian target of rapamycin (mTOR), a serine/threonine kinase that integrates signals about nutrient and energy status with downstream effectors that influence cell division. In addition, we discovered a new interaction involving IQGAP1, mTOR and Akt, which is a downstream target of mTOR. Akt phosphorylation on Ser-473, which is catalyzed by mTOR and required for Akt activation, increased with increasing amounts of IQGAP1, and decreased with IQGAP1 mutation. We hypothesize that IQGAP1 is a scaffold that facilitates mTOR and Akt interaction.